Polyether-based electrolyte for long-life lithium metal battery and preparation method of polyether-based electrolyte
The copolymerization of pentaerythritol tetraacrylate and 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane in the electrolyte improves thermal stability and ion transport, enhancing the performance of lithium metal batteries.
Patent Information
- Application Number
- CN202411320323.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
Existing polyether-based electrolytes for lithium metal batteries suffer from poor thermal stability and slow ion transport, which limits their cycle life and safety.
A polyether-based electrolyte is prepared by copolymerizing pentaerythritol tetraacrylate and 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane to form a polymer matrix with improved thermal stability and ion transport, using a specific molar ratio and polymerization conditions.
The new electrolyte significantly enhances thermal stability, ion conductivity, and cycle life of lithium metal batteries, with high ionic conductivity and prolonged cycle performance, especially in high-nickel ternary batteries.
Smart Images

Figure CN119208722A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium metal batteries, and in particular to a polyether-based electrolyte for long-life lithium metal batteries and a preparation method thereof. Background Art
[0002] Lithium metal batteries with lithium metal anodes and high nickel cathodes and solid or gel polymer electrolytes are expected to achieve higher energy density than lithium-ion batteries. The main structure of the polymer electrolyte significantly affects ion transport and also determines the cycle life and thermal stability of lithium metal batteries. However, the widely used polyether-based electrolytes have a high Li+ / -20% capacity due to the crowded main structure of the polymer and the volatility of some organic matter when heated. + The conduction is slow and the thermal stability is poor. Therefore, by improving the main structure of the polyether-based electrolyte, it is beneficial to improve ion transport and enhance thermal stability.
[0003] At present, there are three main methods to solve the problem of poor thermal stability of polyether-based electrolytes: the first is to use ether monomers with better thermal stability to polymerize or copolymerize to form a polymer main structure with better thermal stability, thereby improving the overall thermal stability of the polyether-based electrolyte; the second is to introduce heteroatoms, such as F, P, Si, etc., into the thermally stable ether monomers to remove oxygen free radicals generated when the polyether-based electrolyte is heated, and delay or prevent the oxidative decomposition of organic matter in the polyether-based electrolyte; however, since some organic matter in the polyether-based electrolyte is easily volatile when heated, it is still difficult to solve the problem of thermal decomposition of the polyether-based electrolyte; the third is to optimize the formula of the organic electrolyte in the polyether-based electrolyte, but its inherent easy decomposition when heated is still difficult to solve.
[0004] Therefore, it remains challenging to develop polyether-based electrolytes that possess both excellent thermal stability and fast ion transport.
[0005] In the prior art, CN116190778A discloses a composition of a gel polymer electrolyte, including an electrolyte and a polymerized monomer, wherein the electrolyte includes a non-aqueous organic solvent and an electrolyte salt, and the gel polymer electrolyte is a gel polymer electrolyte for a lithium ion battery or a sodium ion battery. The polymer monomer is selected from compounds 1-25, wherein compound 24 is 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane. The total mass of the polymerized monomer accounts for 0.1-8% of the mass of the electrolyte. The composition of the gel polymer prepared by the polymerized monomer has a small molecular weight and a small surface tension with the positive and negative electrodes of the lithium / sodium ion battery, so that the composition can fully wet the diaphragm, and can form a good interface contact with the electrode after polymerization, effectively reducing the interface impedance and improving the interface compatibility; at the same time, the elements such as P, Si, F or N introduced into the polymerized monomer enable the gel polymer electrolyte to release free radicals under certain conditions, and these free radicals can capture the oxygen free radicals generated by the decomposition of the battery material, thereby making it difficult for the electrolyte to spontaneously combust. In addition, lithium / sodium ions can react with the polar functional groups (such as F) introduced into the monomer. - , O - ) coordination, with the movement of the polymer chain, lithium / sodium ions continuously jump from one coordination site to another, realizing the transmission of lithium / sodium ions, thereby improving the cycle performance of lithium / sodium ion batteries. However, the gel electrolyte obtained by the polymerization of compound 24 and compound 11 still has the problem of thermal failure in the 150°C hot box test, and the thermal decomposition of the gel electrolyte is still serious, which needs further improvement.
[0006] CN117673458A discloses an in-situ preparation method of a solid-state lithium battery with reaction selectivity. The prepolymer of the solid-state lithium battery is a double-bond functional group or epoxy functional group monomer containing vinyl and acrylic groups, including at least one of acrylate, acrylonitrile, polyethylene glycol diacrylate, methoxyacrylate, acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, glycidyl methacrylate, allyl alcohol glycidyl ether, ethylene carbonate, vinylene carbonate, propylene carbonate, acrylic acid, styrene, siloxane, acetate, 1,3,5-triallyl isocyanurate, triallyl cyanurate, pentaerythritol tetraacrylate, pentaerythritol glycidyl ether, isopentaerythritol tetraacrylate, 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane, and neopentyl glycol dimethacrylate. The lithium salt, polymer, prepolymer and free radical scavenger containing mercapto (vinyl) group are in a mass ratio of 10-50:10-150:50-150:50-150. It improves the room temperature ionic conductivity, interface compatibility and structural accuracy of the polymer electrolyte. It does not solve the problem of the influence of thermal decomposition of the polymer electrolyte on the ionic conductivity. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a polyether-based electrolyte for a long-life lithium metal battery and a preparation method thereof. The main structure of the copolymer formed by copolymerization of pentaerythritol tetraacrylate and 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane improves the thermal stability of the polyether-based electrolyte, especially the thermal decomposition, delays the volatilization of the polyether-based electrolyte, improves the ion transport of the polymer electrolyte and prolongs the service life of the lithium metal battery.
[0008] The technical solution of the present invention is as follows:
[0009] The present invention provides a method for preparing a polyether-based electrolyte for a long-life lithium metal battery, comprising the following steps:
[0010] S1: taking an organic electrolyte, pentaerythritol tetraacrylate and 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane monomer and mixing them evenly to obtain a precursor solution; wherein the mass proportion of 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane monomer in the precursor solution is 0.8-1.0wt%, and the molar ratio of pentaerythritol tetraacrylate to 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane monomer is 1:1;
[0011] S2: uniformly mixing the precursor solution and azobisisobutyronitrile to obtain a mixed solution;
[0012] S3: polymerizing the mixed solution at a temperature above 60° C. for at least 3 hours to obtain a polyether-based electrolyte for a long-life lithium metal battery.
[0013] In a specific embodiment of the present invention, the organic electrolyte is a carbonate electrolyte.
[0014] In a specific embodiment of the present invention, the carbonate electrolyte comprises lithium hexafluorophosphate, ethylene carbonate and ethylene carbonate.
[0015] In a specific embodiment of the present invention, the concentration of lithium hexafluorophosphate in the carbonate electrolyte is 1M.
[0016] In a specific embodiment of the present invention, the volume ratio of the ethylene carbonate to the diethyl carbonate is 1:1.
[0017] In a specific embodiment of the present invention, in step S3, the polymerization reaction temperature is 60-70°C.
[0018] In one embodiment of the present invention, the polymerization temperature is 70°C.
[0019] The present invention discloses a polyether-based electrolyte for a long-life lithium metal battery prepared according to the aforementioned preparation method.
[0020] In a specific embodiment of the present invention, the polyether-based electrolyte for the long-life lithium metal battery has an ionic conductivity of 2.01 mS / cm at 25°C and an ionic conductivity of 2.88 mS / cm at 70°C.
[0021] In one embodiment of the present invention, the degree of polymerization of the polyether-based electrolyte for long-life lithium metal batteries is complete.
[0022] In a specific embodiment of the present invention, the total weight loss rate of the polyether-based electrolyte for long-life lithium metal batteries at 200° C. is ≤35.5%.
[0023] The present invention also provides a high-nickel ternary lithium metal battery, which comprises the aforementioned polyether-based electrolyte for long-life lithium metal batteries. The polyether-based electrolyte for long-life lithium metal batteries is used as the electrolyte of the high-nickel ternary lithium metal battery.
[0024] In a specific embodiment of the present invention, the high-nickel ternary lithium metal battery is preferably a Li||NCM811 battery.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The polyether-based electrolyte for long-life lithium metal batteries of the present invention significantly delays the volatilization of the polyether-based electrolyte by introducing thermally stable copolymer matrix pentaerythritol tetraacrylate and 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane, and can achieve and improve the thermal stability and ion transport of the polyether-based electrolyte for long-life lithium metal batteries, thereby extending the service life of the lithium metal battery.
[0027] 2. The polyether-based electrolyte for the long-life lithium metal battery of the present invention has high ionic conductivity, with an ionic conductivity of 2.01 mS / cm at 25° C. and an ionic conductivity of 2.88 mS / cm at 70° C.
[0028] 3. The polyether-based electrolyte for the long-life lithium metal battery of the present invention has a high ion migration number. According to calculation, the lithium ion migration number is 0.67. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 These are photos of the polyether-based electrolyte prepared in Example 1 of the present invention before and after the polymerization reaction; wherein a is a photo of the mixed solution before the polymerization reaction, and b is a photo of the polyether-based electrolyte after the polymerization reaction;
[0030] Figure 2The Fourier transform infrared (FTIR) spectrum comparison diagram of the polyether-based electrolyte prepared in Example 1 of the present invention and DVTU, PETEA and the precursor solution;
[0031] Figure 3 The thermogravimetric analysis (TGA) and the derivative (DTG) curve comparison diagram of the polyether-based electrolyte and the organic electrolyte prepared in Example 1 of the present invention; wherein a is a thermogravimetric analysis (TGA) curve diagram, and b is a derivative (DTG) curve diagram of TGA;
[0032] Figure 4 The nuclear magnetic resonance spectrum (NMR) of the polyether-based electrolyte and the organic electrolyte prepared in Example 1 of the present invention at room temperature; wherein a is 7 Li NMR diagram, b is 19 F NMR spectra;
[0033] Figure 5 This is a comparison chart of the ionic conductivity of the polyether-based electrolyte and the organic electrolyte prepared in Example 1 of the present invention at 25-70°C;
[0034] Figure 6 The chronoampere curves of the Li||Li symmetric battery of the polyether-based electrolyte and the organic electrolyte prepared in Example 1 of the present invention at a polarization voltage of 10 mV and the AC impedance spectrum before and after polarization (inset); wherein, a is the chronoampere curve of the polyether-based electrolyte and the AC impedance spectrum before and after polarization (inset), and b is the chronoampere curve of the organic electrolyte and the AC impedance spectrum before and after polarization (inset);
[0035] Figure 7 This is a comparison chart of the cycle performance of the Li||NCM811 battery of the polyether-based electrolyte and the organic electrolyte prepared in Example 1 of the present invention at 25°C;
[0036] Figure 8 This is a comparison chart of the cycle performance of Li||NCM811 batteries with polyether-based electrolytes and organic electrolytes prepared in Example 1 of the present invention at 60°C. DETAILED DESCRIPTION
[0037] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0038] The present invention provides a method for preparing a polyether-based electrolyte for a long-life lithium metal battery, comprising the following steps:
[0039] S1: taking an organic electrolyte, pentaerythritol tetraacrylate and 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane monomer and mixing them evenly to obtain a precursor solution; wherein the mass proportion of 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane monomer in the precursor solution is 0.8-1.0wt%, and the molar ratio of pentaerythritol tetraacrylate to 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane monomer is 1:1;
[0040] S2: uniformly mixing the precursor solution and azobisisobutyronitrile to obtain a mixed solution;
[0041] S3: react the mixed solution at above 60°C for at least 3h.
[0042] In the present invention, pentaerythritol tetraacrylate and 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane monomer are copolymerized to obtain the main structure of the polymer electrolyte, which has excellent thermal stability. It can also delay or prevent the thermal decomposition of the organic electrolyte. At the same time, due to the asymmetry and alternating changes between the COC coordination sites in the polyether-based electrolyte, the main structure of the polymer can be adjusted to form an anion-rich solvation structure. This solvation structure can not only maintain the advantages of the ether bond, but also reduce the excessive Li + and electrolytes, enhancing the interaction between anions and electrolytes, thereby promoting rapid Li + Conductivity, improving ion transport in polyether-based electrolytes.
[0043] In some examples, the organic electrolyte is a carbonate electrolyte.
[0044] In some examples, the carbonate electrolyte includes lithium hexafluorophosphate, ethylene carbonate, and ethylene carbonate.
[0045] In some examples, the concentration of lithium hexafluorophosphate in the carbonate electrolyte is 1 M.
[0046] In some examples, the volume ratio of ethylene carbonate to diethyl carbonate is 1:1.
[0047] In some examples, in step S3, the polymerization reaction temperature is 60-70°C.
[0048] In some examples, the polymerization temperature is 70°C.
[0049] The present invention discloses a polyether-based electrolyte for a long-life lithium metal battery prepared according to the aforementioned preparation method.
[0050] In some examples, the polyether-based electrolyte for a long-life lithium metal battery has an ionic conductivity of 2.01 mS / cm at 25° C. and an ionic conductivity of 2.88 mS / cm at 70° C.
[0051] In some examples, the degree of polymerization of the polyether-based electrolyte for long-life lithium metal batteries is complete.
[0052] In some examples, the total weight loss of the polyether-based electrolyte for long-life lithium metal batteries at 200° C. is ≤35.5%.
[0053] The present invention also provides a high-nickel ternary lithium metal battery, which comprises the aforementioned polyether-based electrolyte for long-life lithium metal batteries. The polyether-based electrolyte for long-life lithium metal batteries is used as the electrolyte of the high-nickel ternary lithium metal battery.
[0054] In some examples, the high-nickel ternary lithium metal battery is preferably a Li||NCM811 battery.
[0055] The following is a further description of the substrate implementation mode of the present invention in conjunction with examples, but the present invention is not limited to the scope of the examples.
[0056] Example 1
[0057] The main raw materials of this embodiment include: pentaerythritol tetraacrylate (PETEA), 3,9-divinyl-2,4,8,10-tetraoxaspiro[5,5]undecane (DVTU), azobisisobutyronitrile (AIBN), ethylene carbonate (EC), and diethyl carbonate (DEC).
[0058] The method for preparing the polyether-based electrolyte for the long-life lithium metal battery of this embodiment comprises the following steps:
[0059] 1. Mix EC and DEC in a volume ratio of 1:1, then add LiPF 6 A carbonate electrolyte solution with a concentration of 1 M is prepared;
[0060] 2. Take 21.2 mg (0.85 wt% of the mass of the carbonate electrolyte, 0.83 wt% of the mass of the precursor solution) of DVTU and 35.2 mg (1:1 molar ratio with DVTU) of PETEA, add them to 2.488 g of the carbonate electrolyte and stir evenly to obtain a precursor solution;
[0061] 3. Add 0.1 wt% AIBN to the precursor solution and stir evenly to obtain a mixed solution;
[0062] 4. The mixed solution was polymerized at 70° C. for 3 h to obtain a polyether-based electrolyte for a long-life lithium metal battery.
[0063] In this example, a polyether-based electrolyte was prepared. The photos before and after the polymerization reaction are shown in FIG. Figure 1 As shown; wherein, a is a photograph of the mixed solution before the polymerization reaction, and b is a photograph of the polyether-based electrolyte after the polymerization reaction.
[0064] Example 2
[0065] In this example, the polyether-based electrolyte was prepared according to the steps of Example 1, with the only difference being that the mass of the carbonate electrolyte was adjusted to 2.4 g, the masses of DVTU and PETEA remained unchanged, and the mass percentage of AIBN remained unchanged.
[0066] Example 3
[0067] In this example, the polyether-based electrolyte was prepared according to the steps of Example 1, except that the mass of the carbonate electrolyte was adjusted to 2.6 g, the masses of DVTU and PETEA remained unchanged, and the mass percentage of AIBN remained unchanged.
[0068] Example 4
[0069] In this example, the polyether-based electrolyte was prepared according to the steps of Example 1, except that the mixed solution was polymerized at 65° C. for 3 h.
[0070] Example 5
[0071] In this embodiment, the polyether-based electrolyte was prepared according to the steps of Embodiment 1, except that the mixed solution was polymerized at 75° C. for 3 h.
[0072] The carbonate electrolyte of Example 1 is used as the organic electrolyte to characterize the polyether-based electrolyte for long-life lithium metal batteries prepared in Example 1:
[0073] Depend on Figure 1 As shown, the polyether-based electrolyte for long-life lithium metal batteries is prepared by adding DVTU and PETEA to a carbonate electrolyte, stirring evenly, and then adding AIBN and polymerizing at 70°C.
[0074] Depend on Figure 2 The polymerization of the precursor solution was verified by Fourier transform infrared spectroscopy (FTIR) at 1600-1650 cm -1 In the range, the C=C bending vibration and stretching vibration of the acrylic acid group in DVTU and PETEA were observed, respectively, and no characteristic C=C peak was observed in the polyether-based electrolyte after polymerization, indicating that DVTU and PETEA were successfully cross-linked and cured.
[0075] Depend on Figure 3(a) Thermogravimetric analysis (TGA) was proposed to explore the thermal stability of the polyether-based electrolyte and the organic electrolyte in Example 1. The results showed that when the temperature reached 200°C, the total weight loss rates of the polyether-based electrolyte and the organic electrolyte were 35.5% and 90.4%, respectively. This shows that the introduction of DVTU and PETEA copolymer matrix with good thermal stability into the polyether-based electrolyte can significantly delay the thermal volatilization of the organic electrolyte;
[0076] Depend on Figure 3 (b) The pyrolysis process of the polyether-based electrolyte and the organic electrolyte in Example 1 was analyzed by the derivative TGA (DTG) curve. Specifically, the first stage was the pyrolysis of the organic electrolyte, and the second stage was the pyrolysis of LiPF 6 The fourth stage corresponds to the significant thermal decomposition of the salt, while the decomposition of the copolymer matrix in the polyether-based electrolyte.
[0077] Depend on Figure 4 The nuclear magnetic resonance spectroscopy (NMR) of Li + Solvation structure in polyether-based electrolyte and organic electrolyte in Example 1. Figure 4 (a) 7 Chemical shifts in Li NMR reflect the solvation structure of Li + The polyether-based electrolyte shows a more negative chemical shift (-1.10359 ppm) than the organic electrolyte (-1.04456 ppm) due to the shielding effect of Li + The surrounding electron density increases, which causes Li + The shielding effect of anions and Li + The interactions between them are stronger, thus forming an anion-rich solvation structure. Figure 4 (b) 19 The chemical shifts in F NMR further illustrate the solvation structure information in the polyether-based electrolyte and the organic electrolyte. The chemical shifts in the polyether-based electrolyte are the highest (-69.42 ppm and -71.31 ppm). Compared with the organic electrolyte (-70.09 ppm and -71.97 ppm), the F nuclei in the polyether-based electrolyte are shielded the least, which means that Li + With polyether-based electrolyte Strong coordination.
[0078] Depend on Figure 5It can be seen from the ionic conductivity comparison chart that at 25°C, the ionic conductivity of the polyether-based electrolyte in Example 1 is as high as 2.01 mS / cm, while the ionic conductivity of the organic electrolyte is only 1.47 mS / cm; and with the increase of temperature, the ionic conductivity of the polyether-based electrolyte and the organic electrolyte shows an upward trend, and the rising rate of the polyether-based electrolyte is higher than that of the organic electrolyte; at 70°C, the ionic conductivity of the polyether-based electrolyte in Example 1 is as high as 2.88 mS / cm, while the ionic conductivity of the organic electrolyte is only 2.21 mS / cm, indicating that the polyether-based electrolyte has excellent ionic conductivity.
[0079] Depend on Figure 6 From the chronoamperometric curve of the Li||Li symmetric battery and the AC impedance spectrum before and after polarization (inset), we can see that Figure 6 (a) The lithium ion transfer number (t Li+ =0.67) is significantly higher than Figure 6 (b) Organic electrolyte (t Li+ =0.26), this significant enhancement can be attributed to the anion-rich solvation structure in the polyether-based electrolyte for long-life lithium metal batteries to regulate the rapid Li + Conductivity, various Li in polyether-based electrolytes + The presence of the coordination group accelerates the Li + migration.
[0080] The polyether-based electrolyte prepared in Example 1 was matched with the NCM811 positive electrode and the Li negative electrode to assemble a Li||NCM811 battery. Meanwhile, an organic electrolyte-based Li||NCM811 battery was used as a comparison.
[0081] Depend on Figure 7 It can be seen that the two batteries were subjected to long cycle tests at room temperature 25°C, 0.3C charging and 0.5C discharging conditions. It can be seen that the initial specific capacity of the Li||NCM811 battery with polyether-based electrolyte is 188.4mAh / g, which is significantly higher than the initial specific capacity of the Li||NCM811 battery with organic electrolyte, which is 180.3mAh / g. The battery with polyether-based electrolyte can be stably cycled for more than 700 cycles, and the capacity retention rate is 67.3%. On the contrary, the cycle performance of the organic electrolyte-based Li||NCM811 battery decays rapidly, and the capacity retention rate after 700 cycles is only 9.6%.
[0082] Depend on Figure 8It can be seen that the two batteries were cycled at a high temperature of 60°C and 0.5C charge and discharge conditions. The initial specific capacity of the Li||NCM811 battery with polyether-based electrolyte was 186.9mAh / g, which was significantly higher than the initial specific capacity of the Li||NCM811 battery with organic electrolyte of 174.2mAh / g; the Li||NCM811 battery with polyether-based electrolyte was able to maintain stable cycling for more than 80 cycles, and the capacity retention rate after 80 cycles was 82.2%; on the contrary, the cycling performance of the organic electrolyte-based Li||NCM811 battery decayed rapidly, and the capacity retention rate after 80 cycles was only 50.9%; this shows that improving the main structure of the polyether-based electrolyte is beneficial to enhancing thermal stability and improving the ion transport of lithium metal batteries in high temperature environments.
[0083] The above results demonstrate that the polyether-based electrolyte has the potential to rapidly transfer Li metal into practical lithium metal batteries. + It has remarkable effects in conductivity, high ionic conductivity, high lithium ion transference number, long cycle life and thermal stability.
Claims
1. A method for preparing a polyether-based electrolyte for a long-life lithium metal battery, characterized in that: The preparation of the polyether electrolyte for long-life lithium metal batteries comprises the following steps: S1: taking an organic electrolyte, pentaerythritol tetraacrylate and 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane monomer and mixing them evenly to obtain a precursor solution; wherein the mass proportion of 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane monomer in the precursor solution is 0.8-1.0wt%, and the molar ratio of pentaerythritol tetraacrylate to 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane monomer is 1:1; S2: uniformly mixing the precursor solution and azobisisobutyronitrile to obtain a mixed solution; S3: polymerizing the mixed solution at a temperature above 60° C. for at least 3 hours to obtain a polyether-based electrolyte for a long-life lithium metal battery.
2. The preparation method according to claim 1, characterized in that: The organic electrolyte is a carbonate electrolyte.
3. The preparation method according to claim 2, characterized in that: The carbonate electrolyte contains lithium hexafluorophosphate, ethylene carbonate and ethylene carbonate.
4. The preparation method according to claim 3, characterized in that: The concentration of the lithium hexafluorophosphate in the carbonate electrolyte is 1M.
5. The preparation method according to claim 1, characterized in that: The volume ratio of the ethylene carbonate to the diethyl carbonate is 1:
1.
6. The preparation method according to claim 1, characterized in that: In step S3, the polymerization reaction temperature is 60-70°C; preferably, the polymerization reaction temperature is 70°C.
7. A polyether-based electrolyte for a long-life lithium metal battery prepared by the preparation method according to any one of claims 1 to 6.
8. The polyether-based electrolyte for long-life lithium metal batteries according to claim 7, characterized in that: The ionic conductivity of the polyether-based electrolyte for long-life lithium metal batteries is 2.01 mS / cm at 25° C. and 2.88 mS / cm at 70° C.
9. The polyether-based electrolyte for long-life lithium metal batteries according to claim 7, characterized in that: The polymerization degree of the polyether-based electrolyte for long-life lithium metal batteries is complete; preferably, the total weight loss rate of the polyether-based electrolyte for long-life lithium metal batteries at 200° C. is ≤35.5%.
10. High nickel ternary lithium metal battery, characterized in that: The high-nickel ternary lithium metal battery comprises a polyether-based electrolyte for a long-life lithium metal battery prepared by the preparation method described in any one of claims 1 to 6 or a polyether-based electrolyte for a long-life lithium metal battery described in any one of claims 7 to 9; the high-nickel ternary lithium metal battery is preferably a Li||NCM811 battery.
Citation Information
Patent Citations
Gel polymer electrolyte and composition and battery for preparing electrolyte
CN116190778A
Solid-state lithium battery in-situ preparation method with reaction selectivity and all-solid-state battery thereof
CN117673458A
